SALES AND OPERATIONS PLANNING - Fourie, Fanie (My University, 2011)
This research explores the implementation of a Sales and Operations Planning (S&OP) process in order to observe the results on the performance of the supply chain after an implementation. Based on the literature review, the effectiveness of the supply chain’s performance is often criticised for not being optimal in supporting the complexity of businesses operating in the global environment. In this study, the South African Breweries Limited (SAB) was selected as a case study to explore the implementation of an S&OP process and to examine the theoretical aspects of this model. This research provides an overview supporting the implementation of the S&OP process in the case company. It also highlights the influence that this model had on the improvement in the performance of the supply chain: such as creating ontime- in-full order fulfilment and improving customer service. However, because the model is operational in nature, a brief review is provided to illustrate the challenges faced during financial integration.
MBA - WBS
Keywords: SA Breweries; Sales and salesmanship; Selling; Operations management